- 1-800-665-6601
- [email protected]

We can add 14 on both sides

6x – 14 + 14 = x + 11 + 14

6x = x + 25

Now we can subtract x on both sides

6x – x = x + 25 – x

5x = 25

Divide by 5 on both sides of the above equation, we get, x = 5.

We can add + 6 on both sides of the inequation

7x – 6 + 6 ≤ 43 + 6

7x ≤ 49

Now we can divide by 7, then we get

So the solution of the given inequality is (-∞, 7]. Or

We can write this as x = {……….-3, -2, -1, 0, 1, 2, 3, 4, 5, 6, 7}

We can subtract 1 on both sides of the inequation

3x + 1 – 1 ≥ 13 – 1

3x ≥ 12

Divide by 3, Then we get x≥ 4

We can write the solution as x = {4, 5, 6, 7,……………………}